Synergetic effects of interdisciplinary integratio in ecologi-geographical scientific and methodical works of professor Ilgizar Timergalievich Gaisin - Valentin N. Mikhelkevich; Elena N. Chekanushkina; Nina A. Tymoschuk (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The contribution of the prominent Russian scientist in the field of ecological and geographical education, the doctor of pedagogical sciences, professor Gaysin Ilgizar Timergalievich, in the development of current scientific and pedagogical problem of interdisciplinary integration is considered. The authors analyze his scientific and educational methods, which set forth the fundamental and methodological provisions for the interdisciplinary integration of scientific knowledge, the design and implementation of integrated educational disciplines on the basis of the dominant courses in geography and ecology, as well as interdisciplinary didactic complexes and modules in the structures of slave educational disciplines. The mechanism of interdisciplinary integration is explained. Based on the author's quoted works, the characteristics of the values and merits of interdisciplinary integration as one of the innovative and highly intensive pedagogical technologies are given.The article is dedicated to the 65th anniversary of the outstanding scientist and teacher, professor, Honored Worker of Higher Professional Education of the Russian Federation, Gaisin Ilgizar Timergalievich.